5CN05 partitioning in an aqueous two-phase system: A new approach to the solubilization of hydrophobic drugs - Lopes, Andre Moreni; Santos-Ebinuma, Valeria de Carvalho [UNESP]; Apolinario, Alexsandra Conceicao; Bezerra Mendonca, Francisco Jaime; Goulart de Lima Damasceno, Bolivar Ponciano; Pessoa, Adalberto; Silva, Jose Alexsandro da (Elsevier B.V., 2014)
Liquid-liquid extraction for the purification of molecules has been central to many advances in the pharmaceutical industry. These processes were developed based on the property that some polymer and/or micellar solutions present to separate into a concentrated phase and a diluted phase. Based on the differences in the physical and chemical environments of the two coexisting phases, and since both phases contain approximately 60-90% of water, liquid-liquid extraction provides a powerful alternative to both extract and solubilize a molecule. This paper examines the partition behavior of the synthetic drug, 2-[(3,4-dichlorine-benzylidene)-amino]-5,6-dihydro-4H-cyclopenta[b]thiophene-3-carbonitrile (5CN05), in an aqueous two-phase polymer system (ATPPS) and also in an aqueous two-phase micellar system (ATPMS). The results showed that both systems are favorable for extraction the 5CN05 drug high partition coefficient values (K-5CN05 > 200) and yield (Y-5CN05 > 99.48%) in the concentrated phase were achieved with the systems. However, the ATPPS generated a partition coefficient (K-5CN05) higher than the one obtained with ATPMS. The results suggest that both processes may be used for the extraction and concentration of molecules with hydrophobic characteristics, such as 5CN05. They also provide an optimal environment for the solubilization of such molecules, allowing for greater efficiency when purifying many classes of drugs. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: PEG; Triton X-114; 5CN05; Liquid-liquid extraction; Aqueous two-phase systems